Prevalence of Prediabetes among Adult Population of Dubai, the United Arab Emirates: Findings from Dubai Household Survey, 2019 - Mohamed M. Hassanein; Fatheya F. Alawadi; Heba Mamdouh; Hamid Y. Hussain; Ahmed Khater; Gamal Ibrahim; El-Daw Sulieman (Dubai Diabetes and Endocrinology Journal)
Introduction: The health and social burdens of diabetes mellitus (DM) and prediabetes are steadily increasing worldwide, reflecting the impact of industrial transitions; shifting to unhealthy, sedentary life patterns; and unhealthy food consumption. In the United Arab Emirates (UAE), including the Emirate of Dubai, DM and prediabetes are considered a national public health challenge in terms of extent, impact, cost, and consequences. This study aims to estimate the prevalence of prediabetes and associated risk factors among a representative sample of the adult population in the Emirate of Dubai.